Tribute to Tony Haymet - Laird, B.B.; Bryk, T. (Condensed Matter Physics, 2016)
It is our great pleasure to present a Special issue of Condensed Matter Physics in honour of the renowned scientist and our former scientific advisor Professor A.D.J. "Tony" Haymet, who turned 60 this February. An internationally-known physical chemist and scientific manager with over 170 scientific publications and numerous op-ed pieces, Tony Haymet served from 2006 until 2012 as the Director of the Scripps Institution of Oceanography, Vice Chancellor for Marine Sciences and Dean of the Graduate School of Marine Sciences at the University of California at San Diego (UCSD), where he is currently a Distinguished Professor.